Sudden death in athletes: An analysis of the involvement profile based on case reports (Research, Society and Development, 2025)
Sudden death is defined as an unexpected death that can occur in any individual, including athletes. Its pathophysiology is related to the imbalance between oxygen supply and demand during physical exercise. However, some pre-existing factors and diseases contribute to its occurrence, such as structural and electrical cardiac abnormalities, as well as acquired anomalies, particularly in individuals under thirty-five years of age. In those over thirty-five, coronary artery disease stands out as the main etiology. Considering that most of these conditions are asymptomatic and progress to death, it is extremely important to study the disease’s involvement profile. Therefore, the present study aims to evaluate the causes of sudden cardiac death in order to prevent its occurrence. To this end, a systematic literature review was carried out using the LILACS, SCIELO, PUBMED, and Google Scholar databases. Seventy-two case reports were collected between 2000 and 2024. The results demonstrated a higher involvement of males aged eleven to twenty years. The main etiologies were hypertrophic cardiomyopathy, followed by atherosclerotic coronary artery disease and coronary artery anomalies, confirmed at autopsy. Thus, it is evident that sudden death in athletes arises from underlying diseases, and therefore it is essential to conduct screening to stratify cardiovascular risk, as well as to maintain medical follow-up during regular physical activities, in addition to providing guidance on the risks of anabolic steroid use to prevent the fatal outcome of such an event.